Barriers to guideline‐compliant psoriasis care: analyses and concepts. (4th November 2015) - Eissing, L.; Radtke, M.A.; Zander, N.; Augustin, M.
Abstract: Despite the availability of effective therapeutics and evidence‐based treatment guidelines, a substantial proportion of patients with moderate‐to‐severe psoriasis does not receive appropriate care. This under‐provision of health care may cause further worsening of health, remarkable limitations of the patient's quality of life, and indirect costs for the health care system. In order to provide guideline‐compliant care for every psoriasis patient, it is important to identify barriers obstructing optimal care. Studies have identified various barriers on the physician's and on the patient's side; however, respective studies approached only single barriers, and not all of them in the context of psoriasis. Other publications that describe barriers systematically did not focus on psoriasis either. The objective of this literature review was to identify barriers and facilitators, based on studies analysing quality of care and single barriers, resulting in a comprehensive model of causal factors. Our analyses revealed three categories of barriers – patient‐related, physician‐related and external factors: On the patient side, we found non‐adherence to therapies to be an important barrier, often in close association with psychiatric factors. Barriers on the physician's side predominantly are incomplete knowledge of the guidelines as well as the complexity of psoriasis comorbidity. In some countries, payment for patients with complex disease status is poor and inconsistent reimbursement regulations potentially interfere with optimal care. The current analysis indicates that most barriers are interdependent. Thus, measures approaching related barriers simultaneously are required. To improve care for psoriasis patients, further studies systematically addressing all potentially relevant barriers in conjoint are needed.